Family Counselling Model Based on 3S Values (Sipakatau, Sipakainge, and Sipakalebbi) for Strengthening Positive Character in Junior High School Students - Masdar Bahari; Harmita Sari; Hamka (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to explore the integration of Luwu’s local wisdom values, namely Sipakatau, Sipakainge, and Sipakalebbi (3S), into family counselling as a strategy for strengthening the positive character of junior high school students. The study employed an exploratory qualitative descriptive approach to investigate parents’ experiences and perspectives regarding the implementation of these values in family life. The research participants consisted of parents of junior high school students from a junior high school in Palopo City, South Sulawesi, Indonesia, who were selected through purposive sampling. Data were collected through in-depth interviews and analyzed using thematic analysis techniques. The results showed that the values of Sipakatau, Sipakainge, and Sipakalebbi had been internalized and consistently applied within families through daily interactions. Parents emphasized the importance of mutual respect, guidance, and openness to feedback as key strategies in shaping children’s behavior. The integration of these values contributed to improving the quality of communication within the family and supported the development of positive character traits among students, such as politeness, empathy, responsibility, openness, and emotional control. Despite challenges, including parental workload and external environmental influences, these values remain relevant in the context of contemporary family life. These findings indicate that integrating Luwu’s local wisdom values into family counselling represents a culturally grounded approach that is effective in strengthening character education and optimizing the role of families in student development.